IMPLEMENTASI PROGRAM PENGEMBANGAN MUTU SARANA PRASARANA PERPUSTAKAAN MELALUI PENATAAN RUANG PERPUSTAKAAN SMAN 1 CIOMAS - Suhriyatul Hasanah (Tarbawi, 2017)
In an effort to support the implementation of excellent service or satisfactory then the library as an institution engaged in services need to pay attention to the necessary spatial arrangement in order to realize the prime or satisfactory conditions. Spatial design exist in the library needs to be designed specifically because it is different from the arrangement of space in general. In other words, a library should organize the library space as much as possible, so that the library visitors feel at home to linger in the library. With the arrangement of this library room in the library expected SMAN 1 Ciomas is more developed, as the foundation of educational institutions. This study aims to: 1) help develop the library space management SMAN 1 Ciomas 2) Knowing what constraints contained in the library 3) To increase knowledge, experience, recognition and observation. This research was conducted at a formal educational institution that is SMAN 1 Ciomas. The research method used is qualitative case study, respondents in this research is the head of library and librarian. The results of this study that the development of SMAN 1 Ciomas library has been there developments in the quality of infrastructure facilities through the arrangement of the library space. Keywords. Quality Development, Infrastructure Facilities, and Library Spatial Planning.